2013
DOI: 10.3390/molecules180910095
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Cunninghamella elegans UCP/WFCC 0542 Biomass and Chitosan with Amino Acid Supply

Abstract: Studies were carried out with Cunninghamella elegans UCP/WFCC 0542 to evaluate the effects of an abundant supply of amino acids, asparagine and corn steep liquor associated with sucrose on the production of biomass and chitosan by submerged fermentation. The concentrations of the components of the culture medium which were determined by a 2 3 full factorial design evaluated the interactions and effects of the independent variables of the sucrose, asparagine and corn steep liquor in relation to carbon and nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 31 publications
2
9
1
3
Order By: Relevance
“…Santos et al [10] reported that the increase in biomass production by C. elegans is due to the presence of considerable amounts of amino acids (alanine, arginine, histidine, leucine, lysine, tyrosine, phenylalanine) and vitamins (biotin, choline, inositol, niacin, pyridoxine, thiamine) that are essential for the growth of the microorganism. Edwinoliver et al [29] also suggest that the use of corn steep liquor for lipase production from Aspergillus niger makes the process green, because this substrate is renewable and economically viable on an industrial scale.…”
Section: Resultsmentioning
confidence: 99%
“…Santos et al [10] reported that the increase in biomass production by C. elegans is due to the presence of considerable amounts of amino acids (alanine, arginine, histidine, leucine, lysine, tyrosine, phenylalanine) and vitamins (biotin, choline, inositol, niacin, pyridoxine, thiamine) that are essential for the growth of the microorganism. Edwinoliver et al [29] also suggest that the use of corn steep liquor for lipase production from Aspergillus niger makes the process green, because this substrate is renewable and economically viable on an industrial scale.…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in fermentation technology addressed that many of these problems can be overcome by culturing chitosan-producing fungi, particularly Zygomycetes species, which are known to contain chitosan as natural cell wall component [7]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Valores inferiores de biomassa de C. elegans (IFM 46109) em meio enriquecido com glicose, asparagina e tiamina, também foram relatados por Franco et al (2005), com 11,6 g L -1 . Santos et al (2013) também obtiveram valores menores de biomassa, 16,95 g L -1 , em relação ao presente estudo, ao cultivar C. elegans (UCP/WFCC 0542) em meio composto por milhocina.…”
Section: Produção De Biomassaunclassified
“…Stamford et al (2007), relataram alto rendimento de quitina, 40,09%, contudo, o rendimento de quitosana permaneceu dentro da média, 5,89%. Um rendimento acima da média foi relatado por Santos et al (2013) ao obter 2,14 g L -1 , e aproximadamente 13,8%, de quitosana.…”
Section: Rendimento De Quitina E Quitosanaunclassified
See 1 more Smart Citation